Densities and excess molar volumes of the binary systems of the ionic liquid trihexyl(tetradecyl)phosphonium bromide mixed with acetonitrile or tetrahydrofuran at temperatures from 293.15 to 313.15 K - Elizalde-Solis, Octavio; Zúñiga-Moreno, Abel; Camacho-Camacho, Luis E.; García-Morales, Ricardo; González-Arias, Sandro; Verónico-Sánchez, Francisco J. (Frontiers in Physics, 2023)
Experimental densities and excess molar volumes of two binary mixtures composed of the ionic liquid Trihexyl(tetradecyl)phosphonium bromide ([THTDP][Br]) mixed with acetonitrile (ACN) or tetrahydrofuran (THF) are reported in this work. Measurements were carried out by means of a vibrating tube densimeter at temperatures from (293.15 to 323.15) K at 0.78 bar. Both binary systems were studied in the whole composition range along with the pure compounds. Excess molar volumes were calculated from the experimental densities and were fitted with the Redlich-Kister polynomial equation. Excess molar volumes were negative for the mixtures, and became more negative as the temperature increased. In addition, ERAS model was applied for the modelling of excess molar volumes.